2010
DOI: 10.3189/172756410791386661
|View full text |Cite
|
Sign up to set email alerts
|

Back analysis of drifting-snow measurements over an instrumented mountainous site

Abstract: ABSTRACT. The NEMO numerical model of drifting snow, whose general outlines are presented in this paper, is based on a physical model for saltation and turbulent diffusion. The model needs a set of input parameters including fall velocity, threshold shear velocity, shear velocity, mass concentration and roughness, which are obtained from empirical formulae and wind speed measured at a given height. To better determine the required field data in an alpine context, our experimental site, Col du Lac Blanc (2700 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 37 publications
1
31
0
3
Order By: Relevance
“…This is why we use our RCM here with a high horizontal and vertical resolution. Nevertheless the issues raised concerning the accuracy of the Ingénierie Acoustique & Vibratoire (IAV) FlowCapt acoustic sensors (Chritin et al 1999) used in the present study have, up to now, prevented a reliable quantitative comparison of the blowing snow flux (Cierco et al 2007;Naaim-Bouvet et al 2010). …”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is why we use our RCM here with a high horizontal and vertical resolution. Nevertheless the issues raised concerning the accuracy of the Ingénierie Acoustique & Vibratoire (IAV) FlowCapt acoustic sensors (Chritin et al 1999) used in the present study have, up to now, prevented a reliable quantitative comparison of the blowing snow flux (Cierco et al 2007;Naaim-Bouvet et al 2010). …”
Section: Introductionmentioning
confidence: 95%
“…The calibration of FlowCapt results in overestimation of the blowing snow flux that is all the larger due to the high wind speed (Cierco et al 2007;Naaim-Bouvet et al 2010). As the winds responsible for the transport of blowing snow are very strong in Antarctica, considerable overestimation of the blowing snow flux can be expected.…”
Section: Observationsmentioning
confidence: 99%
“…Les processus physiques en jeu ont pu être étu-diés plus finement pour pouvoir être à terme mieux pris en compte dans les modèles [Naaim-Bouvet F., 2008]. Cette vision reste bien sur schématique car dans le même temps, l'instrumentation permettait également une estimation des Un des paramètres clef, dont la mesure est encore soumise à controverse, est le flux de neige transporté.…”
Section: Le Site Du Col Du Lac Blanc 2000-2010 : De L'observatiounclassified
“…Les premiers résultats obtenus grâce à ce renforcement d'instrumentation ont montrés que [Naaim-Bouvet F., 2008], , : -La proportionnalité de la rugosité aérodynamique avec la vitesse de frottement semble confirmée (figure 9) avec un coefficient de proportionnalité dépendant de l'évènement. Cependant la faible valeur du coefficient de corrélation et la grande variabilité des résultats reste source d'interrogation.…”
Section: Iii2 Vers Une Meilleure Connaissance Des Processus Physiques…unclassified
“…In this study, the observed threshold wind speed was estimated from several relatively long-term snow flux observation data collected by the FlowCapt acoustic sensors, which was designed for continuous and automatic recording of snow flux in the air (Chritin et al, 1999). A number of studies have demonstrated that the FlowCapt sensor is capable of detecting drifting snow or blowing snow (Naaim-Bouvet et al, 2010;Bellot et al, 2011;Das et al, 2012;Trouvilliez et al, 2015). Wind speed required for snow flux to occur and the corresponding snow deposition time and temperature were extracted.…”
Section: Introductionmentioning
confidence: 99%